Implementation of Social Networking Application as a Tool for English Language Learning in Vocational and Boarding School - Eka Widhi Yunarso; Pikir Wisnu Wijayanto; Ismail Ismail (IPTEK Journal of Proceedings Series, 2014)
SMK Al - Aitaam and PERSIS Boarding School is a place in the field of education , which are based on Islamic education . Development of science, technology , language very rapidly at this time also encourages the two educational institutions to incorporate foreign language learning (English) curriculum or guidelines in the learning process that runs in the two institutions. But learning undertaken encountered several problems such as lack of media dynamic learning English , which is always updated, by the changing times, the lack of computer facilities and internet media that can be used by students to add to the English vocabulary . To overcome it offered a solution to support English language learning by designing learning materials covering a wide range of intergrated skills competency which can be accessed free of charge by the students and teachers in the form of a social networking application that allows students improve their English skills by using a variety of features provided , ranging mastery of reading, writing and listening.